Pengaruh Pemberian Air Rebusan Daun Sirih Untuk Mengurangi Keputihan Pada Ibu Hamil - Nuken Rochmadiah Aprianti; Khamidah Khamidah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Betel is a native Indonesian plant that grows creeping or protruding on the trunk of other trees. Not only for ornamental plants, betel leaves are also believed to be able to overcome various diseases. Betel leaf can also be used for vaginal discharge whose healing properties have been clinically tested. A woman is more prone to vaginal discharge during pregnancy because during pregnancy there are hormonal changes which one of the factors is an increase in the amount of fluid production and a decrease in vaginal acidity. Objective: To determine the effect of giving betel leaf boiled water to reduce vaginal discharge in pregnant women. Method: This type of research is a quasy experiment with a non equivalent control group. The study was conducted by providing intervention in the experimental group in the form of betel leaf decoction, while in the control group was not given. Results: In the experimental group, the difference in healing leucorrhoea had an average of 13.1. In the control group, the difference in healing vaginal discharge had an average of 7.9. The results of the statistical test obtained a p value of 0.015 < α (0.05), so there was a difference in the difference in healing leucorrhoea in the experimental and control groups at the Wulan Mardikaningtyas, Amd.Keb PMB in Sukoharjo City (p = 0.015). Conclusion: Betel leaf boiled water is effective for reducing vaginal discharge in pregnant women.